Some Factors Affecting Students’ Academic Achievement: a Study at Nong Lam University Ho Chi Minh City - Ho, Hồ Văn Công Nhân; Vo, Võ Văn Việt; Huynh, Huỳnh Trung Chánh (Journal of Technical Education Science, 2024)
This study was conducted to identify and evaluate the factors affecting the academic achievement of students at Nong Lam University - Ho Chi Minh City. A quantitative study design was applied. Primary data was collected through questionnaire survey method. There were 855 students, selected by convenience sampling technique, who voluntarily agreed to participate in the study. Research data was processed by descriptive statistics and inferential statistics on the statistical software SPSS 22.0 to answer the research questions. Descriptive statistics such as frequency, mean, standard deviation, and percentage were used to describe the study data. Research results show that the factors related to lecturers and facilities are assessed by students as good and meet teaching requirements. In addition, the analysis shows that there is a strong correlation between faculty factors and student achievement. There was no statistically significant difference between parents’ marital status, parents’ education level, family economy, and academic performance.